Positive electrode active material, positive electrode including the same, and lithium secondary battery

JP2025022867AActive Publication Date: 2025-02-14SAMSUNG SDI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024128607
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-03
Filing Date
2024-08-05
Publication Date
2025-02-14
Estimated Expiration
2044-08-05

AI Technical Summary

Benefits of technology

【0008】 一実施形態による正極活物質は、生産価格を最小化しながら容量を極大化したものであって、長寿命特性が確保され、高電圧での電解質との副反応が抑制される。前記正極活物質を適用したリチウム二次電池は、高電圧駆動条件でも高い初期充放電容量および効率を示すことができ、長寿命特性を達成することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022867000001_ABST
    Figure 2025022867000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode active material including a lithium nickel-manganese complex oxide, in which the characteristics of high capacity and high energy density are secured while reducing the price of a positive electrode material, the side reaction with an electrolyte at high voltage is suppressed, and the high-voltage performance is improved, a positive electrode including this positive electrode active material, and a lithium secondary battery.SOLUTION: A positive electrode active material includes: a first positive electrode active material containing a lithium nickel-manganese complex oxide in which the content of nickel is 60 mol% or more relative to 100 mol% of the entire metals excluding lithium and in a mode of a secondary particle formed by aggregation of a plurality of primary particles, the average particle diameter (D50) of the secondary particle is 10 μm to 20 μm; a second positive electrode active material containing a lithium nickel-manganese complex oxide in which the content of nickel is 60 mol% or more relative to 100 mol% of the entire metals excluding lithium and in a monoparticulate mode, the average particle diameter (D50) of the monoparticle is 2 μm to 8 μm; and a third positive electrode active material in a particulate form containing a lithium transition metal phosphorus oxide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material, and a positive electrode and a lithium secondary battery each containing the same. [Background technology]

[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, notebook computers, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage power sources for hybrid and electric vehicles.

[0003] In order to realize a lithium secondary battery suitable for such applications, various positive electrode active materials have been studied. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, while the demand for large-sized, high-capacity, or high-energy density lithium secondary batteries has recently increased sharply, it is expected that the supply of positive electrode active materials containing cobalt, a rare metal, will be extremely short. In other words, since cobalt is expensive and the remaining reserves are not large, it is necessary to develop a positive electrode active material that excludes cobalt or has a reduced cobalt content. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a positive electrode active material containing a lithium nickel-manganese composite oxide, which ensures high capacity and high energy density characteristics while drastically reducing the price of the positive electrode material, and has improved high voltage performance by suppressing side reactions with an electrolyte at high voltage. The present invention also provides a positive electrode active material and a lithium secondary battery containing the same. [Means for solving the problem]

[0005] In one embodiment, the present invention contains a lithium nickel-manganese composite oxide in which the nickel content is 60 mol % or more relative to 100 mol % of all metals excluding lithium, and the secondary particles are formed by agglomeration of a plurality of primary particles, and the average particle size (D 50 The first positive electrode active material has an average particle diameter (D) of 10 μm to 20 μm, and a lithium nickel-manganese composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium, and the single particles are in the form of a single particle. 50 and a third positive electrode active material in the form of particles containing a lithium transition metal phosphate.

[0006] In another embodiment, a positive electrode is provided that includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above.

[0007] In another embodiment, a lithium secondary battery is provided that includes the positive electrode, the negative electrode, and an electrolyte. Effect of the Invention

[0008] The positive electrode active material according to one embodiment maximizes capacity while minimizing production costs, ensures long-life characteristics, and suppresses side reactions with the electrolyte at high voltages. A lithium secondary battery using the positive electrode active material can exhibit high initial charge / discharge capacity and efficiency even under high-voltage driving conditions, and can achieve long-life characteristics. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a scanning electron microscopy (SEM) image of a first positive electrode active material of Example 1. [Diagram 3] 1 is a SEM image of a second positive electrode active material of Example 1. [Figure 4] 1 is a SEM image of a third positive electrode active material of Example 1. [Diagram 5] 13 is an SEM image of a third positive electrode active material of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below so that those skilled in the art can easily implement the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.

[0011] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.

[0012] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.

[0013] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.

[0014] In the drawings, the thickness of layers and regions is exaggerated to clearly show them, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, or plate is said to be "on" another part, this includes not only the case where the part is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" the other part, it means that there is no other part between them.

[0015] Here, the term "layer" includes not only shapes formed on the entire surface when observed in a plan view, but also shapes formed on a portion of the surface.

[0016] The average particle size can be measured by methods well known to those skilled in the art, for example, by using a particle size analyzer, or by using a transmission electron microscope image or a scanning electron microscope image. Alternatively, it can be measured using a dynamic light scattering method, and data analysis can be performed to count the number of particles for each particle size range, and the average particle size can be calculated based on the result. Unless otherwise defined, the average particle size is the diameter (D 50 In addition, unless otherwise defined, the average particle size is determined by measuring the size (diameter or major axis length) of 20 or more randomly selected particles in a scanning electron microscope image to obtain a particle size distribution, and calculating the diameter (D 50 ) may be taken as the average particle size.

[0017] Here, "or" is not to be construed as exclusive; for example, "A or B" is to be construed as including A, B, A+B, etc.

[0018] The term "metal" is understood to include general metals, transition metals, and metalloids (semimetals).

[0019] positive electrode active material In one embodiment, the present invention contains a lithium nickel-manganese composite oxide in which the nickel content is 60 mol % or more relative to 100 mol % of all metals excluding lithium, and the secondary particles are formed by agglomeration of a plurality of primary particles, and the average particle size (D 50 The first positive electrode active material has an average particle diameter (D) of 10 μm to 20 μm, and a lithium nickel-manganese composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium, and the single particles are in the form of a single particle. 50and a third positive electrode active material in the form of particles containing a lithium transition metal phosphate.

[0020] Recently, as the price of cobalt, a rare metal, has soared, there is a demand for the development of positive electrode active materials that exclude cobalt or that have a reduced cobalt content. Among them, positive electrode active materials with a spinel crystal structure, such as lithium manganese oxide (LMO), have a limited capacity due to the small amount of lithium that can be utilized within the structure. Layered nickel-manganese positive electrode active materials can increase the amount of lithium within the structure, making them suitable as materials for high-capacity batteries with excellent capacity and efficiency characteristics. However, the removal of cobalt, which plays a key role in the layered structure, reduces structural stability, increases resistance, and makes it difficult to ensure long life characteristics. In addition, the removal of cobalt accelerates side reactions between the positive electrode active material and the electrolyte under high voltage and high temperature conditions, increasing the amount of gas generated and reducing life characteristics.

[0021] In one embodiment, a first positive electrode active material containing a lithium nickel-manganese composite oxide and in the form of secondary particles having a size of 10 μm to 20 μm is mixed with a second positive electrode active material in the form of single particles having a size of 2 μm to 8 μm, and then a third positive electrode active material containing a lithium transition metal phosphate, which is a low-cost material, is mixed therewith to provide a positive electrode active material that achieves high capacity and high energy density, long life characteristics, and improved high voltage performance.

[0022] The average particle size of the secondary particles of the first positive electrode active material (D 50 ) is the average particle diameter (D 50 In this case, the first positive electrode active material can be expressed as a large grain or a large particle, and the second positive electrode active material can be expressed as a small grain or a small particle. The average particle diameter (D 50 ) is the average particle size (D 50) The capacity and energy density can be maximized and high voltage characteristics can be improved by appropriately mixing large particles in the form of secondary particles and small particles in the form of single particles as the lithium nickel-manganese oxide and additionally mixing lithium transition metal phosphate.

[0023] Here, the average particle size is determined by measuring the size (diameter or major axis length) of 20 or so particles randomly taken from a scanning electron microscope image of the positive active material to obtain a particle size distribution, and then calculating the diameter (D 50 ) may be taken as the average particle size.

[0024] The average particle size (D 50 The average particle diameter (D 50 The particles of the third positive electrode active material may be a type of primary particle, and the average particle size (D 50 ) may be, for example, 10 nm to 2 μm, for example, 50 nm to 1.5 μm, 100 nm to 1.0 μm, 100 nm to 900 nm, or 100 nm to 600 nm. When the average particle size of each positive electrode active material satisfies the above range, high capacity can be achieved and energy density can be maximized.

[0025] The first positive electrode active material may be included at 60% to 90% by weight, the second positive electrode active material may be included at 5% to 35% by weight, and the third positive electrode active material may be included at 5% to 35% by weight, relative to a total of 100% by weight of the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material. As a specific example, the first positive electrode active material may be included at 60% to 85% by weight, the second positive electrode active material may be included at 10% to 25% by weight, and the third positive electrode active material may be included at 5% to 20% by weight. When the mixing ratio of each positive electrode active material satisfies the above range, the energy density can be further increased while increasing the capacity.

[0026] The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material may be the same or different. The nickel content in each lithium nickel-manganese composite oxide is 60 mol% or more relative to 100 mol% of the total metals excluding lithium in the lithium nickel-manganese composite oxide, and may be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be achieved and structural safety can be improved even if the cobalt content is reduced.

[0027] The manganese content may be, for example, 10 mol% to 40 mol% relative to 100 mol% of all metals excluding lithium in the lithium nickel-manganese composite oxide, such as 10 mol% to 39 mol%, 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc. When the manganese content satisfies the above range, the positive electrode active material can achieve high capacity while improving structural stability.

[0028] The lithium nickel-manganese-based composite oxide in each of the first and second positive electrode active materials may be a lithium nickel-manganese-aluminum-based composite oxide further containing aluminum in addition to nickel and manganese. When the composite oxide contains aluminum, it is advantageous to maintain a stable layered structure even if the cobalt element is excluded from the structure. The content of aluminum relative to 100 mol% of the lithium nickel-manganese-aluminum-based composite oxide may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%. When the aluminum content satisfies the above range, a stable layered structure can be maintained even if cobalt is excluded, and the problem of the structure collapsing due to charging and discharging can be suppressed, and the long life characteristics of the positive electrode active material can be achieved.

[0029] The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material may each be independently represented by Chemical Formula 1 below.

[0030] [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 In the chemical formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.4, 0≦z1≦0.03, 0≦w1≦0.3, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.

[0031] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2 may hold. Further, Chemical Formula 1 may contain aluminum, and in this case, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 can be satisfied. For example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 can be satisfied.

[0032] In Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79 may hold, 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3 may hold, 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019 may hold, and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09 etc. may hold.

[0033] The lithium nickel - manganese composite oxide may be a cobalt - free compound that does not contain cobalt or contains a very small amount of cobalt. That is, the lithium nickel - manganese composite oxide of the first positive electrode active material and the lithium nickel - manganese composite oxide of the second positive electrode active material may each independently have a cobalt content of 0 mol% to 0.01 mol% based on 100 mol% of the total metal excluding lithium.

[0034] First positive electrode active material According to an embodiment, the aluminum concentration may be uniform in the secondary particles of the first positive active material excluding the coating layer. That is, the aluminum concentration gradient may be from the center to the surface in the particle, or the aluminum concentration in the outside of the particle is not higher or lower than the inside, and the aluminum in the particle is uniformly distributed. This may be a structure obtained by synthesizing a composite oxide using nickel-manganese-aluminum hydroxide as a precursor by using an aluminum raw material in the preparation of a precursor without additionally doping aluminum in the synthesis process of the positive active material. That is, it may be said that the aluminum content in the inside of the primary particle is the same or similar regardless of the position of the primary particle. If the primary particle is selected at an arbitrary position in the cross section of the secondary particle and the aluminum content in the inside of the primary particle, not the interface of the primary particle, is measured, it may be expressed that the aluminum content is the same / similar / uniform regardless of the position of the primary particle, that is, whether the primary particle is close to the center or the surface of the secondary particle. In this structure, a stable layered structure can be maintained even if cobalt is absent or present in a very small amount, and aluminum by-products and aluminum aggregates are not generated, so that the capacity, efficiency, and life characteristics of the positive electrode active material can be improved simultaneously.

[0035] According to an embodiment, the first positive electrode active material may further include a coating layer containing aluminum and zirconium located on a surface of the secondary particle. By including an aluminum-zirconium-rich layer on the surface of the first positive electrode active material, a side reaction with an electrolyte at a high voltage may be effectively suppressed, and thus the capacity and life characteristics at a high voltage may be improved.

[0036] The aluminum content of the coating layer may be 0.1 mol% to 2 mol%, and the zirconium content of the coating layer may be 0.05 mol% to 1 mol%, based on 100 mol% of the total metals excluding lithium in the first positive electrode active material. The aluminum content of the coating layer in the first positive electrode active material may be, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. The aluminum or zirconium content in the coating layer may be measured, for example, through SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the coating layer satisfies the above range, a thin and uniform coating layer can be formed, and the resistance of the positive electrode active material is not increased, and side reactions with the electrolyte are effectively suppressed, thereby improving the life characteristics of a lithium secondary battery at a high voltage.

[0037] The zirconium content of the coating layer of the first positive electrode active material may be, for example, 0.1 mol% to 1 mol%, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, or 0.1 mol% to 0.6 mol%. When the zirconium content is within this range, the positive electrode active material does not decrease in capacity or increase in resistance, and a good coating layer is formed to effectively suppress side reactions with the electrolyte, and the capacity characteristics and life characteristics under high voltage driving conditions may be further improved.

[0038] The coating layer of the first positive electrode active material may further include yttrium in addition to aluminum and zirconium. In this case, the content of yttrium may be 0.1 mol % to 1 mol % based on 100 mol % of all metals excluding lithium of the first positive electrode active material.

[0039] The coating layer of the first positive electrode active material may be in the form of a film that continuously surrounds the surface of the secondary particle, for example, in the form of a shell that surrounds the entire surface of the secondary particle. This is different from a structure in which only a part of the surface of the secondary particle is partially coated. According to one embodiment, the coating layer may be formed to a very thin and uniform thickness while being formed in a form that entirely surrounds the surface of the secondary particle, so that the positive electrode active material has improved structural stability without increasing resistance or decreasing capacity, side reactions with the electrolyte may be effectively suppressed, and the amount of gas generation under high voltage and high temperature conditions may be reduced, thereby achieving long life characteristics.

[0040] The thickness of the coating layer of the first positive electrode active material may be 30 nm to 500 nm, for example, 30 nm to 450 nm, 30 nm to 400 nm, 30 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the coating does not increase resistance or decrease capacity, and the structural stability of the positive electrode active material can be improved and side reactions with the electrolyte can be effectively suppressed. The thickness of the coating layer can be measured, for example, through TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured through a TEM-EDS line profile.

[0041] The coating layer of the first positive active material is characterized by being thin, at a thickness of several tens to several hundreds of nanometers, but uniform in thickness. For example, the deviation in thickness of the coating layer within one positive active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation in thickness of the coating layer refers to the thickness of the coating layer within one positive active material particle. The deviation in thickness of the coating layer may be, for example, a value obtained by measuring the thickness at 10 or more points in an electron microscope image of a cross section of one positive active material particle, calculating the arithmetic average, dividing the absolute value of the difference between one data and the arithmetic average value by the arithmetic average value, and multiplying the result by 100. The deviation or standard deviation in thickness of the coating layer satisfies the above range means that a coating layer of uniform thickness is well formed in the form of a film on the surface of the positive active material particle, thereby improving the structural stability of the positive active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.

[0042] Meanwhile, aluminum may be diffused into the secondary particles during the formation of the coating layer. Thus, the positive electrode active material according to an embodiment may further include a grain boundary coating portion containing aluminum and located on the surface of the primary particle inside the secondary particle. The interior of the secondary particle may refer to the entire interior except for the surface of the secondary particle, or may refer to a region from the surface of the secondary particle to about 60% of the radius in the direction toward the center of the secondary particle. The grain boundary coating portion is a concept distinct from the coating layer on the surface of the secondary particle, and refers to a coating portion formed on the surface of the primary particle located inside the secondary particle. The presence of the grain boundary coating portion may be confirmed by SEM-EDS analysis of a cross section of the positive electrode active material. The formation of the aluminum grain boundary coating portion may further stabilize the structure of the positive electrode active material, thereby improving the life characteristics.

[0043] The aluminum content in the grain boundary coating portion is not particularly limited, and as an example, the aluminum content in the grain boundary coating portion may be less than the aluminum content in the coating layer.

[0044] Meanwhile, the aluminum content of the coating layer of the first positive electrode active material may be higher than the aluminum content of the coating layer of the second positive electrode active material described later. For example, the aluminum content of the coating layer of the first positive electrode active material and the aluminum content of the coating layer of the second positive electrode active material may be 5:1 to 2:1, or 4:1 to 2:1 in molar ratio. In this case, the aluminum of the coating layers of the first and second positive electrode active materials does not act as a resistor, and the capacity and life characteristics at high voltages can be maximized while improving the structural stability of each.

[0045] Second positive electrode active material The term "single particle" of the second positive electrode active material means that the particle exists alone without a grain boundary and is made of one particle, and may mean a single particle, a monolith structure, a single body structure, or a non-aggregated particle in which the particles are not aggregated with each other in terms of morphology, and may be, for example, a single crystal.

[0046] The second positive electrode active material may further include an aluminum-containing coating layer located on the surface of the single particle, which may improve initial discharge capacity and life characteristics at high voltage.

[0047] The aluminum content in the coating layer of the second positive electrode active material may be 0.1 mol% to 2 mol% based on 100 mol% of the total metals excluding lithium in the second positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. This means only the content of aluminum contained in the coating layer separately from the aluminum contained inside the single particle. The aluminum content in the coating layer may be measured, for example, through SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the coating layer satisfies the above range, it is possible to form a thin and uniform coating layer, and the resistance of the positive electrode active material is not increased, and side reactions with the electrolyte are effectively suppressed, thereby improving the life characteristics of the lithium secondary battery under high voltage and high temperature conditions. For example, if the aluminum content of the coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, resulting in reduced charge / discharge efficiency and reduced life characteristics. Conversely, if the aluminum content of the coating layer is too low, a coating layer of appropriate thickness may not be formed, resulting in reduced effectiveness in suppressing side reactions with the electrolyte.

[0048] The coating layer of the second positive electrode active material may further include yttrium, in which case the side reaction between the positive electrode active material and the electrolyte at high voltage may be more effectively suppressed to improve the life characteristics. The yttrium content in the coating layer is 0.1 mol% to 1 mol% with respect to 100 mol% of the total metals excluding lithium in the second positive electrode active material, and may be, for example, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, 0.1 mol% to 0.6 mol%, 0.1 mol% to 0.4 mol%, or 0.1 mol% to 0.3 mol%. When the yttrium content satisfies the above range, the positive electrode active material does not decrease in capacity or increase in resistance, and a good coating layer is formed to effectively suppress the side reaction with the electrolyte, and the amount of gas generation can be effectively reduced under high voltage or high temperature conditions.

[0049] The coating layer of the second positive electrode active material may be in the form of a film that continuously surrounds the surface of the single particle, for example, in the form of a shell that surrounds the entire surface of the single particle. This is different from a structure in which only a part of the surface of the particle is partially coated. According to one embodiment, the coating layer may be formed in a form that entirely surrounds the surface of the single particle, but with a very thin and uniform thickness, so that the positive electrode active material has improved structural stability without increasing resistance or decreasing capacity, and side reactions with the electrolyte may be effectively suppressed, thereby achieving long life characteristics at high voltage.

[0050] The thickness of the coating layer of the second positive electrode active material may be 30 nm to 500 nm, for example, 30 nm to 450 nm, 30 nm to 400 nm, 30 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the coating does not increase resistance or decrease capacity, and the structural stability of the positive electrode active material can be improved and side reactions with the electrolyte can be effectively suppressed. The thickness of the coating layer can be measured, for example, through TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured through a TEM-EDS line profile.

[0051] The coating layer of the second positive electrode active material is characterized by being thin, at a thickness of several tens to several hundreds of nanometers, but uniform in thickness. For example, the deviation in thickness of the coating layer within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation in thickness of the coating layer refers to the thickness of the coating layer within one positive electrode active material particle. The deviation in thickness of the coating layer may be, for example, a value obtained by measuring the thickness at 10 or more points in an electron microscope image of a cross section of one positive electrode active material particle, calculating the arithmetic average, dividing the absolute value of the difference between one data and the arithmetic average value by the arithmetic average value, and multiplying the result by 100. The deviation or standard deviation in thickness of the coating layer satisfies the above range means that a coating layer of uniform thickness is well formed in the form of a film on the surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.

[0052] In the coating layer of the second positive electrode active material, aluminum may exist in a continuous film form, and yttrium may exist in an island form, depending on the characteristics of each element.

[0053] In one embodiment, aluminum and yttrium may be mixed in one coating layer, and in this case, aluminum may be present in the form of a continuous film and yttrium may be present in the form of islands, but the forms are not limited thereto.

[0054] In another embodiment, aluminum and yttrium may each form a separate layer. For example, the second positive electrode active material may include a first coating layer containing aluminum located on the surface of the single particle, and a second coating layer containing yttrium located on the first coating layer. Aluminum may first be attached or absorbed on the surface of the single particle to form a first coating layer in the form of a thin film, and then yttrium may be coated on the first coating layer to form a second coating layer. Of course, aluminum and yttrium may be mixed in the first coating layer and the second coating layer, but it can be said that the first coating layer is an aluminum-rich coating layer mainly composed of aluminum, and the second coating layer is an yttrium-rich coating layer mainly composed of yttrium. In this case, yttrium may be present in the second coating layer in the form of islands, but is not particularly limited.

[0055] The thicknesses of the first coating layer and the second coating layer are not particularly limited, but the thickness of the first coating layer may be 10 nm to 200 nm, for example, 20 nm to 200 nm, 30 nm to 200 nm, or 30 nm to 180 nm. The thickness of the second coating layer may be 20 nm to 300 nm, for example, 20 nm to 250 nm, 20 nm to 200 nm, 30 nm to 300 nm, or 50 nm to 300 nm. When each thickness satisfies the above range, the coating does not increase resistance or decrease capacity, and the structural stability of the positive electrode active material is improved, and side reactions with the electrolyte are effectively suppressed to improve life characteristics at high voltage.

[0056] Third positive electrode active material The lithium transition metal phosphate of the third positive electrode active material can include, for example, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, lithium titanium phosphate, or combinations thereof.

[0057] The lithium transition metal phosphate of the third positive electrode active material can specifically be represented by Chemical Formula 3, Chemical Formula 4, Chemical Formula 5, Chemical Formula 6, or Chemical Formula 7.

[0058] [Chemical Formula 3] Li a3 Fe (1-x3) M 3 x3 PO4 In Chemical Formula 3, 0.90 ≦ a3 ≦ 1.5 and 0 ≦ x3 ≦ 0.4, and M 3 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or a combination thereof.

[0059] The compound represented by Chemical Formula 3 is lithium iron phosphate. In Chemical Formula 3, for example, 0.90 ≦ a3 ≦ 1.2, or 0.95 ≦ a3 ≦ 1.1, and 0 ≦ x3 ≦ 0.3, 0 ≦ x3 ≦ 0.2, 0 ≦ x3 ≦ 0.1, or 0 < x3 ≦ 0.05. For example, when a3 = 1 and x3 = 0, Chemical Formula 3 can be expressed as LiFePO4.

[0060] [Chemical Formula 4] Li a4 Mn x4 Fe (1-x4-y4) M 4 y4 PO4 In Chemical Formula 4, 0.90 ≦ a4 ≦ 1.5, 0.1 ≦ x4 ≦ 0.9, 0.1 ≦ y4 ≦ 0.9, and M 4 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or a combination thereof.

[0061] The compound represented by Chemical Formula 4 is lithium manganese iron phosphate. In Chemical Formula 4, for example, 0.90 ≦ a4 ≦ 1.2, or 0.95 ≦ a4 ≦ 1.1, and 0.2 ≦ x4 ≦ 0.8, 0.3 ≦ x4 ≦ 0.7, or 0.4 ≦ x4 ≦ 0.6. The compound represented by Chemical Formula 4 is, for example, LiMn 0.9 Fe 0.1 PO4, LiMn 0.8 Fe 0.2PO4, LiMn 0.7 Fe 0.3 PO4, LiMn 0.6 Fe 0.4 PO4, LiMn 0.5 Fe 0.5 PO4, LiMn 0.4 Fe 0.6 PO4, LiMn 0.3 Fe 0.7 PO4, LiMn 0.2 Fe 0.8 PO4, or LiMn 0.1 Fe 0.9 It may be PO4 or the like.

[0062] [Chemical formula 5] Li a5 Mn (1-x5) M 5 x5 PO4 In Chemical formula 5, 0.90 ≤ a5 ≤ 1.5, 0 ≤ x5 ≤ 0.4, and M 5 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or a combination thereof.

[0063] The compound represented by Chemical formula 5 is a lithium manganese phosphate. In Chemical formula 5, for example, 0.90 ≤ a5 ≤ 1.2, or 0.95 ≤ a5 ≤ 1.1 may hold, and 0 ≤ x5 ≤ 0.3, 0 ≤ x5 ≤ 0.2, 0 ≤ x5 ≤ 0.1, or 0 < x5 ≤ 0.05 may hold. For example, when a5 = 1 and x5 = 0, Chemical formula 5 can be expressed as LiMnPO4.

[0064] [Chemical formula 6] Li a6 Ti (2-x6) M 6 x6 (PO4)3 In Chemical formula 6, 0.90 ≤ a6 ≤ 1.5, 0 ≤ x6 ≤ 0.4, and M 6 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or a combination thereof.

[0065] The compound represented by Chemical Formula 6 is a lithium titanium phosphate. In Chemical Formula 6, for example, 0.90 ≦ a6 ≦ 1.2, or 0.95 ≦ a6 ≦ 1.1 can hold, and 0 ≦ x6 ≦ 0.3, 0 ≦ x6 ≦ 0.2, 0 ≦ x6 ≦ 0.1, or 0 < x6 ≦ 0.05 can hold. For example, when a6 = 1 and x6 = 0, Chemical Formula 6 can be represented as LiTi2(PO4)3.

[0066] [Chemical Formula 7] Li a7 Ti (1-x7) M 7 x7 PO5 In Chemical Formula 7, 0.90 ≦ a7 ≦ 1.5 and 0 ≦ x7 ≦ 0.4, and M 7 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or a combination thereof.

[0067] The compound represented by Chemical Formula 7 is a lithium titanium phosphate. In Chemical Formula 7, for example, 0.90 ≦ a7 ≦ 1.2, or 0.95 ≦ a7 ≦ 1.1 can hold, and 0 ≦ x7 ≦ 0.3, 0 ≦ x7 ≦ 0.2, 0 ≦ x7 ≦ 0.1, or 0 < x7 ≦ 0.05 can hold. For example, when a7 = 1 and x7 = 0, Chemical Formula 7 can be represented as LiTiPO5.

[0068] As a specific example, the lithium transition metal phosphate of the third positive electrode active material is LiFePO4, LiMn 0.7 Fe 0.3 PO4, LiMn 0.6 Fe 0.4 PO4, LiMn 0.5 Fe 0.5 PO4, LiMn 0.4 Fe 0.6 PO4, LiMn 0.3 Fe 0.7 PO4, LiMnPO4, LiTiPO5, LiTi2(PO4)3, or a combination thereof.

[0069] In the positive electrode active material according to an embodiment, the content of cobalt may be, for example, 0.01 mol % or less, 0.005 mol % or less, 0.001 mol % or less, for example, 0 mol % to 0.01 mol %, based on 100 mol % of all metals excluding lithium. The positive electrode active material according to an embodiment may be, for example, a cobalt-free positive electrode active material.

[0070] In addition, the positive electrode active material according to an embodiment may be characterized as being sodium-free. Although sodium ions may be used in the manufacturing process of a positive electrode active material in general, a manufacturing method described below may be used to form positive electrode active material particles with a stable structure and a coating layer with a uniform thickness without using sodium ions.

[0071] Method for producing positive electrode active material In one embodiment, the present invention provides a method for producing a positive electrode active material, including: (i) mixing a nickel-manganese composite hydroxide having a nickel content of 60 mol % or more relative to 100 mol % of the total metals and a lithium raw material, and heat-treating the mixture to prepare a first positive electrode active material in the form of secondary particles formed by aggregation of a plurality of primary particles; (ii) mixing a nickel-manganese composite hydroxide having a nickel content of 60 mol % or more relative to 100 mol % of the total metals and a lithium raw material, and heat-treating the mixture to prepare a second positive electrode active material in the form of single particles; (iii) preparing a third positive electrode active material containing a lithium transition metal phosphate; and (iv) mixing the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material.

[0072] In the respective preparation processes of the first positive electrode active material and the second positive electrode active material, the nickel-manganese-based composite hydroxide may contain no or a very small amount of cobalt, and may be, for example, a cobalt-free nickel-manganese-based composite hydroxide, for example, a cobalt-free nickel-manganese-aluminum-based composite hydroxide. The nickel-manganese-based composite hydroxide may be prepared by a general coprecipitation method.

[0073] The nickel content in the nickel-manganese composite hydroxide is 60 mol% or more relative to 100 mol% of the total metal, and may be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be achieved, and structural safety can be improved even if the cobalt content is reduced.

[0074] The manganese content in the nickel-manganese composite hydroxide may be 10 mol% to 40 mol%, 10 mol% to 39 mol%, 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc., relative to 100 mol% of the total metal.

[0075] When the nickel-manganese composite hydroxide further contains aluminum, the aluminum content may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%, based on 100 mol% of the total metal. When the manganese and aluminum contents in the composite hydroxide are within the above ranges, the structural safety of the positive electrode active material can be improved while achieving high capacity, and the production cost can be reduced to improve economic efficiency.

[0076] In the nickel-manganese composite hydroxide, the cobalt content may be 0.01 mol% or less, 0.005 mol% or less, or 0.001 mol% or less, based on 100 mol% of the total metal. Such nickel-manganese composite hydroxide is economical because it can avoid the increase in unit price due to cobalt, and it can be said to have maximized capacity and improved structural stability.

[0077] The nickel-manganese composite hydroxide can be represented, for example, by the following Chemical Formula 2.

[0078] [Chemical formula 2] Nix2 Mn y2 Al z2 M 2 w2 (OH)2 In chemical formula 2, 0.6≦x2≦0.8, 0.1≦y2≦0.40≦z2≦0.03, 0≦w2≦0.3, and 0.9≦x2+y2+z2+w2≦1.1; M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr.

[0079] In Formula 2, for example, 0.6≦x2≦0.8, 0.1≦y2≦0.39, 0.01≦z2≦0.03, and 0≦w2≦0.29.

[0080] In the preparation process of the first positive electrode active material, aluminum is not additionally doped, and instead, aluminum raw material is used in the preparation of the precursor, so that a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly dispersed within the structure can be used as the precursor. By using such a precursor, a positive electrode active material in which a layered structure is stably maintained even after repeated charging and discharging without the need for cobalt can be prepared, and since aluminum by-products or aluminum aggregates are not formed, the capacity, efficiency characteristics, and life characteristics of the positive electrode active material can be improved.

[0081] In the process of preparing the first positive electrode active material, the nickel-manganese composite hydroxide and the lithium raw material may be mixed in a molar ratio of 1:0.9 to 1:1.8, for example, 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2. The heat treatment after the mixing may be performed in an oxygen atmosphere, for example, at a temperature range of 750°C to 950°C, or 780°C to 900°C, or 810°C to 890°C, for 2 hours to 20 hours, or 4 hours to 12 hours. A lithium nickel-manganese composite oxide can be obtained through the heat treatment. The obtained composite oxide may contain nickel at 60 mol% or more, for example, 60 mol% to 80 mol%, relative to 100 mol% of the total metal, and may contain no cobalt or a very small amount of cobalt of 0.01 mol% or less.

[0082] According to an embodiment, the method for manufacturing a positive electrode active material may further include a step of coating the lithium nickel-manganese composite oxide obtained in the first positive electrode active material preparation process. The lithium nickel-manganese composite oxide has a significantly different content of residual lithium on the particle surface from existing nickel-based oxides of other compositions, such as lithium nickel-cobalt-manganese composite oxide and lithium nickel-cobalt-aluminum composite oxide, and has many different surface properties, making it impossible to form a good coating layer with a uniform film shape using existing coating methods. According to an embodiment, a method is proposed for improving high voltage characteristics by forming a uniform coating layer with a very thin thickness on the surface of a lithium nickel-manganese composite oxide having a very small cobalt content and a nickel content of 60 mol% or more. For example, an aluminum raw material is mixed in an aqueous solvent, and then the lithium nickel-manganese composite oxide is mixed, followed by drying and reheating to form a coating layer according to an embodiment. This can be called a wet coating method.

[0083] The aqueous solvent may include distilled water, an alcohol-based solvent, or a combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. As an example, the aluminum raw material may include aluminum sulfate, which is advantageous in forming a coating layer having a uniform thickness on the surface of the lithium nickel-manganese composite oxide particles. The aluminum content in the aluminum raw material may be designed to be 0.1 mol% to 2 mol% with respect to 100 mol% of the total metals excluding lithium in the first positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%.

[0084] The solution in which the aluminum raw material is mixed with the aqueous solvent may have a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese composite oxide may be added to the aqueous solvent in which the aluminum raw material is mixed and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The pH value of the mixed solution after stirring may be 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous for a coating layer of uniform thickness to be formed.

[0085] The reheat treatment can be understood as a process for forming a coating layer, and can be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 hours to 20 hours, or 3 hours to 10 hours.

[0086] In order to coat the product with zirconium as well as aluminum, a zirconium raw material may be added to the product after the drying process and then heat-treated again. The zirconium raw material may be, for example, zirconium oxide, and may be added so that the zirconium content is 0.05 mol% to 1 mol% relative to 100 mol% of the metals excluding lithium in the first positive electrode active material.

[0087] In the preparation process of the second positive electrode active material, the nickel-manganese composite hydroxide and the lithium raw material may be mixed in a molar ratio of 1:0.9 to 1:1.8, for example, 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2. The heat treatment after mixing may be performed in an oxygen atmosphere, for example, at a temperature range of 750°C to 950°C, or 780°C to 900°C, or 810°C to 890°C, for 2 hours to 20 hours, or 4 hours to 12 hours. The lithium nickel-manganese composite oxide can be obtained through the heat treatment. The obtained composite oxide may contain nickel at 60 mol% or more, for example, 60 mol% to 80 mol%, relative to 100 mol% of the total metal, and may contain no cobalt or a very small amount of 0.01 mol% or less. In order to obtain a single particle form, a process of pulverization may be further included after the production of the lithium nickel-manganese composite oxide.

[0088] The process of preparing the second positive electrode active material may also include a process of mixing nickel-manganese composite hydroxide and a lithium raw material, heat-treating the mixture to obtain single particles containing lithium nickel-manganese composite oxide, and then coating the single particles. It is not possible to directly apply an existing coating method to coat aluminum on the single-particle second positive electrode active material, and a good coating layer having a uniform film shape can be formed by applying a wet coating method according to an example. That is, the obtained single-particle lithium nickel-manganese composite oxide is mixed in a solution of an aqueous solvent and an aluminum raw material, and then dried and heat-treated again to produce the second positive electrode active material.

[0089] The aqueous solvent and the aluminum raw material are as described above. The aluminum content in the aluminum raw material may be designed to be 0.1 mol% to 2 mol% with respect to 100 mol% of all metals excluding lithium in the second positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%.

[0090] When the aluminum raw material is added to the aqueous solvent, the yttrium raw material may be added together to coat Al and Y. The yttrium raw material may include, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide, or a combination thereof. The yttrium content in the yttrium raw material may be designed to be 0.1 mol% to 1 mol% with respect to 100 mol% of the total metals excluding lithium in the second positive electrode active material, for example, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, 0.1 mol% to 0.6 mol%, 0.1 mol% to 0.4 mol%, or 0.1 mol% to 0.3 mol%. By designing the content of the coating raw materials within the above ranges, a coating layer having a thin thickness of tens to hundreds of nanometers and a uniform thickness can be formed, and the amount of gas generated by the lithium secondary battery under high voltage driving conditions can be reduced, and high capacity and long life characteristics can be improved.

[0091] The solution in which the aluminum raw material and the selective yttrium raw material are mixed in an aqueous solvent may have a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese composite oxide is dropped into the aqueous solvent in which the aluminum raw material and the yttrium raw material are mixed and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The pH value of the mixed solution after stirring may be 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous for a coating layer of uniform thickness to be formed.

[0092] Drying after the mixing process can be understood as a process of removing the solvent, and can be performed, for example, at 40°C to 240°C, 100°C to 220°C, or 150°C to 200°C. Reheat treatment can be understood as a process of forming a coating layer, and can be performed, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 hours to 20 hours, or 3 hours to 10 hours. The reheat treatment temperature may be lower than the previous heat treatment temperature, and the reheat treatment time may be the same as or shorter than the previous heat treatment time. By performing reheat treatment under such conditions, a desired coating layer can be obtained.

[0093] The first positive electrode active material, the second positive electrode active material, and the third positive electrode active material may be mixed so that the first positive electrode active material is included in 60 wt% to 90 wt%, the second positive electrode active material is included in 5 wt% to 35 wt%, and the third positive electrode active material is included in 5 wt% to 35 wt%, relative to a total of 100 wt%. As a specific example, the first positive electrode active material may be included in 60 wt% to 85 wt%, the second positive electrode active material is included in 10 wt% to 25 wt%, and the third positive electrode active material is included in 5 wt% to 20 wt%. When the positive electrode active materials are mixed in the above ratios, the energy density can be maximized while increasing the capacity.

[0094] positive electrode In one embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above. The positive electrode active material layer may further include other types of positive electrode active materials in addition to the positive electrode active materials described above. The positive electrode active material layer may also optionally include a binder, a conductive agent, or a combination thereof.

[0095] According to one embodiment, the loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 For example, 10 mg / cm 2 ~30mg / cm 2 or 10 mg / cm 2~20mg / cm 2 In addition, the density of the positive electrode active material layer in the final rolled positive electrode may be 3.4 g / cc to 3.7 g / cc, for example, 3.5 g / cc to 3.6 g / cc or 3.5 g / cc to 3.58 g / cc. When applying the positive electrode active material according to an embodiment, it is advantageous to achieve such a loading level and positive electrode density, and a positive electrode satisfying the loading level and positive electrode density in the above ranges is suitable for achieving a lithium secondary battery with a high capacity and high energy density.

[0096] binder The binder serves to adhere the positive electrode active material particles to each other well and to adhere the positive electrode active material to the current collector well. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.

[0097] Conductive Agent The conductive agent is used to impart electrical conductivity to the electrode, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed can be used. Examples of the conductive agent include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, and the like in the form of metal powder or metal fiber; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0098] The content of the binder and the conductive agent may be 0.5% by weight to 5% by weight, or 0.5% by weight to 3% by weight, respectively, relative to 100% by weight of the positive electrode active material layer.

[0099] The positive electrode current collector can be made of Al, but is not limited to this.

[0100] negative electrode The negative electrode can include a current collector and a negative electrode active material layer located on the current collector, the negative electrode active material layer including a negative electrode active material and can further include a binder, a conductive agent, or a combination thereof.

[0101] negative electrode active material The negative electrode active material includes a material capable of reversibly inserting / extracting lithium ions, lithium metal, a lithium metal alloy, a material capable of being doped and dedoped with lithium, or a transition metal oxide.

[0102] The material capable of reversibly inserting / extracting lithium ions may be a carbon-based negative electrode active material, and may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, and calcined coke.

[0103] As the lithium metal alloy, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.

[0104] As the substance capable of doping and undoping lithium, a Si-based negative electrode active material or a Sn-based negative electrode active material can be used. As the Si-based negative electrode active material, silicon, a silicon-carbon composite, SiOx (0 < x < 2), a Si-Q alloy (wherein Q is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof can be used. As the Sn-based negative electrode active material, Sn, SnO2, a Sn alloy, or a combination thereof can be used.

[0105] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle diameter (D 50 ) of the silicon-carbon composite particles can be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite can be in a form in which silicon particles and amorphous carbon are coated on the surface of the silicon particles. For example, it can include secondary particles (cores) formed by granulating primary silicon particles, and an amorphous carbon coating layer (shell) located on the surface of the secondary particles. The amorphous carbon is also located between the primary silicon particles, and for example, the primary silicon particles can be coated with amorphous carbon. The secondary particles can be dispersed and present in an amorphous carbon matrix.

[0106] The silicon-carbon composite may further contain crystalline carbon. For example, the silicon-carbon composite may include a core containing crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. Examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, and calcined coke.

[0107] When the silicon-carbon composite contains silicon and amorphous carbon, the content of silicon may be 10% to 50% by weight based on 100% by weight of the silicon-carbon composite, and the content of amorphous carbon may be 50% to 90% by weight. When the composite contains silicon, amorphous carbon, and crystalline carbon, the content of silicon may be 10% to 50% by weight based on 100% by weight of the silicon-carbon composite, the content of crystalline carbon may be 10% to 70% by weight, and the content of amorphous carbon may be 20% to 40% by weight.

[0108] Also, the thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle diameter (D 50 ) of the silicon particles (primary particles) may be 10 nm to 1 μm, or 10 nm to 200 nm. The silicon particles may exist alone as silicon, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented by SiO x (0 < x < 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation may be 99:1 to 33:67. In this specification, unless otherwise defined, the average particle diameter (D 50 ) means the diameter of the particle with a cumulative volume of 50% in the particle size distribution.

[0109] The Si-based negative electrode active material or the Sn-based negative electrode active material can be used by mixing with a carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material is mixed with the carbon-based negative electrode active material, the mixing ratio may be 1:99 to 90:10 by weight.

[0110] binder The binder serves to effectively adhere the negative active material particles to each other and to the current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0111] Non-aqueous binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymers, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or combinations thereof.

[0112] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0113] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used.

[0114] The dry binder is a polymeric material capable of being fiberized, and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.

[0115] Conductive Agent The conductive agent is used to impart electrical conductivity to the electrode, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed can be used. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0116] The content of the negative electrode active material may be 95% to 99.5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight relative to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive agent.

[0117] Current collector The negative electrode current collector can include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and can be in the form of a foil, sheet, or foam. The thickness of the negative electrode current collector can be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.

[0118] electrolyte The electrolyte for a lithium secondary battery can be, by way of example, an electrolytic solution, which can include a non-aqueous organic solvent and a lithium salt.

[0119] The non-aqueous organic solvent serves as a medium through which the ions involved in the electrochemical reactions of the battery can migrate. The non-aqueous organic solvent may be a carbonate-, ester-, ether-, ketone-, or alcohol-based solvent, an aprotic solvent, or a combination thereof.

[0120] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone solvent include cyclohexanone. Examples of the alcohol solvent include ethyl alcohol and isopropyl alcohol. Examples of the aprotic solvent include nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes.

[0121] The non-aqueous organic solvent may be used alone or in combination of two or more kinds. When two or more kinds are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which is widely understood by those working in the field.

[0122] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of 1:1 to 1:9.

[0123] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate solvent and an aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.

[0124] The electrolyte may further contain a vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate based compound to improve the battery life.

[0125] Representative examples of the ethylene carbonate-based compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0126] Lithium salts are substances dissolved in organic solvents and act as a source of lithium ions in the battery to enable basic lithium secondary battery operation and to facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).

[0127] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate ion conductivity and viscosity, and therefore can exhibit excellent performance and allow lithium ions to migrate effectively.

[0128] Lithium secondary battery In one embodiment, a lithium secondary battery is provided that includes the positive electrode, the negative electrode, and the electrolyte described above.

[0129] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, etc. types according to their shapes. Fig. 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. Referring to Fig. 1, a lithium secondary battery 100 may include an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).

[0130] The lithium secondary battery according to an embodiment may be suitable for being charged at a high voltage or driven at a high voltage. For example, the charging voltage of the lithium secondary battery may be 4.3 V to 4.6 V, or 4.40 V to 4.55 V. By applying the positive electrode active material according to an embodiment, the lithium secondary battery may significantly reduce the amount of gas generated even when charged at a high voltage, and may achieve high capacity and long life characteristics.

[0131] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multi-layer film of two or more layers of these may be used, and it is of course possible to use a mixed multi-layer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator.

[0132] The separator may include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.

[0133] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyether sulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.

[0134] The porous substrate can have a thickness of about 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.

[0135] The organic material may include a (meth)acrylic copolymer including a first structural unit derived from a (meth)acrylamide, and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or a (meth)acrylate, and a structural unit derived from (meth)acrylamidosulfonic acid or a salt thereof.

[0136] The inorganic substances are Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH) 2、 The inorganic particles may include, but are not limited to, inorganic particles selected from boehmite and combinations thereof. The average particle size (D 50 ) may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.

[0137] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.

[0138] The thickness of each of the coating layers may be from 0.5 μm to 20 μm, for example, from 1 μm to 10 μm, or from 1 μm to 5 μm.

[0139] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.

[0140] Example 1 1. Manufacturing of positive electrode active material (1) Preparation of the first positive electrode active material Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed in a molar ratio of 1:1.05 and subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to obtain a composition of Li 1.05 Ni 0.75 Mn0.23 Al 0.02 O2 and the average particle size (D 50 A first composite oxide having a secondary particle shape with a particle size of about 14 μm was prepared.

[0141] Aluminum sulfate was added to a distilled water solvent, and then the first composite oxide was added thereto and mixed for about 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 1.0 mol% relative to 100 mol% of the total metals excluding lithium in the final first positive electrode active material. The mixed solution was dried at 190°C after removing the solvent, and zirconium oxide was added to the obtained material, and a second heat treatment was performed at 825°C for 8 hours in an oxygen atmosphere to produce a first positive electrode active material. The zirconium content in the zirconium oxide was designed to be 0.2 mol% relative to 100 mol% of the total metals excluding lithium in the final first positive electrode active material. Figure 2 shows an SEM image of the first positive electrode active material produced. The average particle size (D 50 ) is approximately 14 μm.

[0142] (2) Preparation of the second positive electrode active material Ni 0.75 Mn 0.25 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and heat-treated in an oxygen atmosphere at 850℃ for 8 hours to obtain a composition of LiNi 0.75 Mn 0.23 Al 0.02 O2 and the average particle size (D 50 A second composite oxide having a single particle shape and a particle size of about 3 μm was produced.

[0143] Aluminum sulfate and yttrium nitrate were mixed into a distilled water solvent, and then the second composite oxide was added and mixed for 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 0.4 mol% relative to 100% by weight of the total metals excluding lithium in the final second positive electrode active material, and the yttrium content in the yttrium nitrate was designed to be 0.1 mol%. The solvent was removed from the mixed solution, which was then dried at 190°C and then heat-treated at 825°C for 8 hours in an oxygen atmosphere to produce a second positive electrode active material. Figure 3 shows an SEM image of the produced second positive electrode active material. The average particle size (D 50 ) is approximately 3.5 μm.

[0144] (3) Preparation of the third positive electrode active material The average particle size of the primary particles is (D 50 ) is about 200 nm. Figure 4 shows an SEM image of the third positive electrode active material.

[0145] (4) Manufacturing the final positive electrode active material A final positive electrode active material was prepared by mixing 70% by weight of the first positive electrode active material, 20% by weight of the second positive electrode active material, and 10% by weight of the third positive electrode active material.

[0146] 2. Manufacturing of the positive electrode 98.5 wt% of the prepared positive electrode active material, 1.0 wt% of polyvinylidene fluoride binder, and 0.5 wt% of carbon nanotube conductive agent were mixed to prepare a positive electrode active material layer slurry, which was then coated on an aluminum foil current collector, dried, and rolled to prepare a positive electrode. The density of the final rolled positive electrode was about 3.46 g / cc.

[0147] 3. Manufacturing of lithium secondary batteries A negative electrode active material layer slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene butadiene rubber in an aqueous solvent. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and rolled to prepare a negative electrode.

[0148] A polytetrafluoroethylene separator was used, and a lithium secondary battery was fabricated in a conventional manner using an electrolyte prepared by dissolving 1M LiPF6 in a solvent containing a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.

[0149] Example 2 The third positive electrode active material has an average particle size of primary particles (D 50 ) is about 180 nm 0.6 Fe 0.4 Except for using PO4, a positive electrode and a lithium secondary battery were manufactured in substantially the same manner as in Example 1. FIG. 5 is a SEM image of the third positive electrode active material of Example 2.

[0150] Comparative Example 1 A positive electrode and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 1, except that the second positive electrode active material was not mixed, and a mixture of 80 wt % of the first positive electrode active material and 20 wt % of the third positive electrode active material was used as the positive electrode active material.

[0151] Comparative Example 2 A positive electrode and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 2, except that the second positive electrode active material was not mixed, and a mixture of 80 wt % of the first positive electrode active material and 20 wt % of the third positive electrode active material was used as the positive electrode active material.

[0152] Comparative Example 3 A positive electrode and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 1, except that the third positive electrode active material was not mixed, and a mixture of 70 wt % of the first positive electrode active material and 30 wt % of the second positive electrode active material was used as the positive electrode active material.

[0153] For ease of understanding, the design details of the positive electrode active materials in the examples and comparative examples are summarized in Table 1 below.

[0154] [Table 1]

[0155] Evaluation example 1 The lithium secondary batteries manufactured in the examples and comparative examples were initially charged and discharged at a constant current of 0.2 C at 25° C. up to an upper limit voltage of 4.45 V and at a constant voltage of 0.05 C, and then discharged at 0.2 C to an end voltage of 3.0 V, and the initial discharge capacity was shown in Table 1. Next, a cycle of charging at 1.0 C and discharging at 1.0 C in the voltage range of 3.0 V to 4.45 V at 45° C. was repeated 50 times or more, and the ratio of the 50 cycle discharge capacity to the initial discharge capacity was calculated and shown in Table 1.

[0156] Table 1 also shows the positive electrode mixture density in the rolled state for the examples and comparative examples.

[0157] Referring to Table 1, it can be seen that the Examples have a higher positive electrode mixture density than the Comparative Examples, and are more excellent in capacity characteristics and life characteristics when driven at a high voltage of 4.45 V. Comparative Examples 1 and 2 have a lower positive electrode mixture density than the Examples, and are shown to have a lower initial discharge capacity when driven at a high voltage.

[0158] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]

[0159] 100: Lithium secondary battery 10: Positive electrode 20: Negative electrode 30: Separator 40: Electrode assembly 50: Case

Claims

1. The present invention contains a lithium nickel-manganese composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium, and is in the form of secondary particles formed by agglomeration of a plurality of primary particles, and the average particle diameter (D 50 ) is 10 μm to 20 μm; The present invention comprises a lithium nickel-manganese composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium, and the oxide is in the form of a single particle, and the average particle diameter (D 50 ) is 2 μm to 8 μm; and A third positive electrode active material in the form of particles containing lithium transition metal phosphate. A positive electrode active material comprising:

2. The average particle size (D 50 2. The positive electrode active material according to claim 1, wherein the thickness of the first and second electrodes is 10 nm to 2 μm.

3. 2. The positive electrode active material according to claim 1, wherein the first positive electrode active material is contained in an amount of 60% by weight to 90% by weight, the second positive electrode active material is contained in an amount of 5% by weight to 35% by weight, and the third positive electrode active material is contained in an amount of 5% by weight to 35% by weight, relative to a total of 100% by weight of the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material.

4. The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are the same or different, and each independently has a nickel content of 60 mol% to 80 mol% relative to 100 mol% of all metals excluding lithium. The positive electrode active material according to claim 1.

5. the lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are each independently a lithium nickel-manganese-aluminum composite oxide further containing aluminum in addition to nickel and manganese, 2. The positive electrode active material according to claim 1, wherein the content of aluminum in the lithium nickel-manganese-aluminum based composite oxide is 0.1 mol % to 3 mol % relative to 100 mol % of all metals excluding lithium.

6. The positive electrode active material according to claim 1, wherein the lithium nickel-manganese composite oxide of the first positive electrode active material, the lithium nickel-manganese composite oxide of the second positive electrode active material, and the lithium transition metal phosphate of the third positive electrode active material each independently have a cobalt content of 0 mol % to 0.01 mol % relative to 100 mol % of all metals excluding lithium.

7. The lithium nickel-manganese composite oxide of the first positive electrode active material and the lithium nickel-manganese composite oxide of the second positive electrode active material are each independently represented by the following chemical formula 1: [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 In the chemical formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.4, 0≦z1≦0.03, 0≦w1≦0.3, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.

8. 8. The positive electrode active material according to claim 7, wherein, in Chemical Formula 1, 0.6≦x1≦0.8, 0.1≦y1≦0.39, 0.01≦z1≦0.03, and 0≦w1≦0.29 are satisfied.

9. The first positive electrode active material further includes a coating layer that is located on a surface of the secondary particle and contains aluminum, 2. The positive electrode active material of claim 1, wherein the aluminum content of the coating layer is 0.1 mol % to 2 mol % based on 100 mol % of all metals excluding lithium in the first positive electrode active material.

10. 10. The cathode active material of claim 9, wherein the coating layer further comprises zirconium, yttrium, or a combination thereof.

11. 11. The positive electrode active material of claim 10, wherein the coating layer further contains 0.05 mol % to 1 mol % zirconium, and / or 0.05 mol % to 1 mol % yttrium, based on 100 mol % of metals excluding lithium in the first positive electrode active material.

12. The positive electrode active material of claim 9 , wherein the coating layer of the first positive electrode active material has a shell shape that continuously surrounds the surfaces of the secondary particles.

13. The cathode active material according to claim 9 , wherein the coating layer of the first cathode active material has a thickness of 30 nm to 500 nm.

14. The positive electrode active material of claim 9 , wherein the first positive electrode active material further comprises a grain boundary coating portion located on a surface of the primary particle inside the secondary particle and containing aluminum.

15. the second positive electrode active material further includes a coating layer located on a surface of the single particle and containing aluminum; 2. The positive electrode active material of claim 1, wherein the aluminum content of the coating layer is 0.1 mol % to 2 mol % based on 100 mol % of all metals excluding lithium in the second positive electrode active material.

16. The positive electrode active material of claim 15 , wherein the coating layer of the second positive electrode active material is in the form of a shell that continuously surrounds a surface of the single particle.

17. The cathode active material of claim 15, wherein the coating layer of the second cathode active material has a thickness of 30 nm to 500 nm.

18. the coating layer of the second positive electrode active material further contains yttrium; The positive electrode active material of claim 15, wherein the coating layer has an yttrium content of 0.1 mol % to 1 mol % relative to 100 mol % of all metals excluding lithium in the second positive electrode active material.

19. 20. The cathode active material of claim 18, wherein in the coating layer of the second cathode active material, aluminum is present in a continuous film form and yttrium is present in an island form.

20. 20. The cathode active material of claim 18, wherein the second cathode active material comprises a first coating layer located on a surface of the single particle and containing aluminum, and a second coating layer located on the first coating layer and containing yttrium.

21. 2. The cathode active material of claim 1, wherein the lithium transition metal phosphate of a third cathode active material comprises lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, lithium titanium phosphate, or a combination thereof.

22. The positive electrode active material of claim 1 , wherein the lithium transition metal phosphate of the third positive electrode active material is represented by Chemical Formula 3, Chemical Formula 4, Chemical Formula 5, Chemical Formula 6, or Chemical Formula 7: [Chemical formula 3] Li a3 Fe (1-x3) M 3 x3 PO 4 In Chemical Formula 3, 0.90≦a3≦1.5, 0≦x3≦0.4, M 3 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or a combination thereof; [Chemical formula 4] Li a4 Mn x4 Fe (1-x4-y4) M 4 y4 PO 4 In chemical formula 4, 0.90≦a4≦1.5, 0.1≦x4≦0.9, 0.1≦y4≦0.9, M 4 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or a combination thereof; [Chemical formula 5] Li a5 Mn (1-x5) M 5 x5 PO 4 In Chemical Formula 5, 0.90≦a5≦1.5, 0≦x5≦0.4, M 5 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or a combination thereof; [Chemical formula 6] Li a6 Today (2-x6) M 6 x6 (PO 4 ) 3 In Chemical Formula 6, 0.90≦a6≦1.5, 0≦x6≦0.4, M 6 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or a combination thereof; [Chemical formula 7] Li a7 Today (1-x7) M 7 x7 PO 5 In Chemical Formula 7, 0.90≦a7≦1.5, 0≦x7≦0.4, M 7 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr, or combinations thereof.

23. The lithium transition metal phosphate of the third positive electrode active material is LiFePO 4 , LiMn 0.7 Fe 0.3 P.O. 4 , LiMn 0.6 Fe 0.4 P.O. 4 , LiMn 0.5 Fe 0.5 P.O. 4 , LiMn 0.4 Fe 0.6 P.O. 4 , LiMn 0.3 Fe 0.7 P.O. 4 , LiMnPO 4 , LiTiPO 5 , LiTi 2 (P.O. 4 ) 3 or a combination thereof.

24. A positive electrode current collector, and a positive electrode active material layer located on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 23.

25. 25. The positive electrode of claim 24, wherein the positive electrode active material layer has a density of 3.4 g / cc to 3.7 g / cc.

26. The positive electrode according to claim 24 . a negative electrode, and A lithium secondary battery containing an electrolyte.

27. The lithium secondary battery according to claim 26, wherein the charging voltage is 4.3V to 4.6V.

Citation Information

Patent Citations

  • Positive electrode material and lithium ion battery containing same

    CN111682185A

  • Positive electrode active material for lithium-ion secondary cell

    WO2013154142A1